FINANCIAL TECHNOLY UNTUK MENINGKATKAN KEUANGAN INKLUSIF UMKM (Universitas Wijayakusuma Purwokerto, 2023)
The purpose of this community service activity is to improve the knowledge of MSME entrepreneurs in Maruyung Village, Padaherang District, Pangandaran Regency. Entrepreneurs can use one of several types of financial technology products, one of which is non-cash payments, through this service activity. This non-cash payment is also one of Bank Indonesia's programs aimed at digitizing transactions. Our service team had the opportunity to assist MSME business actors in the Maruyung village area on this occasion. We assist by inviting our students to accompany us. We involve FEB Unwiku students with the goal of exposing them to the real world of business in order for them to gain experience. Community service activities were carried out for two months, from November 2022 to December 2022. Community service had very positive benefits. Despite the fact that it is still in the experimental phase, MSME business actors are interested in implementing non-cash payments. Business actors are attempting to integrate digital marketing in addition to using non-cash payments. The usage of financial technology items has a minimal effect on the criminals. They anticipate that using a financial technology solution will boost their company's revenue and expand MSME enterprises' access to credit. The service team's ability to formulate a number of issues from the MSME activities in Maruyung Village and present them as research topics is another effect of this activity. This is an opportunity for students to contribute some of their knowledge. They can observe firsthand experience in MSME enterprises to supplement the information they learn in lectures